Content of Care in 15, 000 Sick Child Consultations in Nine Lower‐Income Countries. (7th March 2018) - Kruk, Margaret E.; Gage, Anna D.; Mbaruku, Godfrey M.; Leslie, Hannah H.
Abstract : Objective: Describe content of clinical care for sick children in low‐resource settings. Data Sources: Nationally representative health facility surveys in Haiti, Kenya, Malawi, Namibia, Nepal, Rwanda, Senegal, Tanzania, and Uganda from 2007 to 2015. Study Design: Clinical visits by sick children under 5 years were observed and caregivers interviewed. We describe duration and content of the care in the visit and estimate associations between increased content and caregiver knowledge and satisfaction. Principal Findings: The median duration of 15, 444 observations was 8 minutes; providers performed 8.4 of a maximum 24 clinical actions per visit. Content of care was minimally greater for severely ill children. Each additional clinical action was associated with 2 percent higher caregiver knowledge. Conclusions: Consultations for children in nine lower‐income countries are brief and limited. A greater number of clinical actions was associated with caregiver knowledge and satisfaction.